Comparison of genome sequencing and clinical genotyping for pharmacogenes. Issue 4 (18th August 2016) - Yang, W; Wu, G; Broeckel, U; Smith, CA; Turner, V; Haidar, CE; Wang, S; Carter, R; Karol, SE; Neale, G; Crews, KR; Yang, JJ; et al.
Abstract : We compared whole exome sequencing (WES, n = 176 patients) and whole genome sequencing (WGS, n = 68) and clinical genotyping (DMET array‐based approach) for interrogating 13 genes with Clinical Pharmacogenetics Implementation Consortium (CPIC) guidelines. We focused on 127 CPIC important variants: 103 single nucleotide variations (SNV), 21 insertion/deletions (Indel), HLA‐B alleles, and two CYP2D6 structural variations. WES and WGS provided interrogation of nonoverlapping sets of 115 SNV/Indels with call rate >98%. Among 68 loci interrogated by both WES and DMET, 64 loci (94.1%, confidence interval [CI]: 85.6–98.4%) showed no discrepant genotyping calls. Among 66 loci interrogated by both WGS and DMET, 63 loci (95.5%, CI: 87.2–99.0%) showed no discrepant genotyping calls. In conclusion, even without optimization to interrogate pharmacogenetic variants, WES and WGS displayed potential to provide reliable interrogation of most pharmacogenes and further validation of genome sequencing in a clinical lab setting is warranted.